Como aprendem os que ensinam e como ensinam os que aprendem?: um estudo com professoras no contexto do jogo traverse - Fiorot, Meire Andersan (2006)
This study aimed at checking the relation between the way the teachers learn and teach in a context of rules game, as well as investigate their reflections on pedagogical practice. Four teachers from the fourth grade of private primary schools in the state of Espírito Santo were subjects of the research. The research was carried out in three situations. (1) in the first one, there was an interview in order to characterize the teachers´ profiles and their conceptions about the learning and teaching processes; (2) the learning situation was composed of stages of instruction, experimentation and problem-solving activity, all of them, making use of the rules game called Traverse; and (3) the teaching situation, composed of the instruction and experimentation phases, once more using the same game. This third situation counted on the participation of four children. During the learning and teaching situations, several questions were proposed so that the teachers could reflect on the situations experienced in the game, their actions and the relations between these ones and the pedagogical practice. The results provided the researcher with the conceptions of the teachers about some themes related to the teaching and learning process, as well as the conflicts the teachers experienced in the school routine. Besides, the researcher could note an evolution in their level of comprehension of the logical system of the game, with the existence of intermediate moments that indicate a partial awareness of the action. The main difficult presented in the process was the comprehension of inter systemic dialetics existing in the game and the simultaneous observation of the teachers´ own actions and the ones of the oponents. Concerning the teaching of the game, there was a predominance of procedures based in the model used by the researcher, having some difficulties been identified on the teachers either at the time of instructing or at mediating. After this analysis, it was possible to establish a parallel between the learning and teaching situations. In this way, it made it possible for the researcher to note that the main obstacles faced by the teachers to advance in their levels of comprehension of the game, during the learning situation, were repeated at the time of teaching. Taking this analysis to the school context, the researcher could also observe the tensions experienced by the teachers when facing the contradictions of the school environment, which involved similar aspects to the ones presented in their difficulties in the game context. The results confirmed the hypothesis that there is a relation between the way the teachers learn and the way they teach in the Traverse game, and that this game can be a rich resource to be used in a context of teacher development. It is suggested a deeper reflection on the contexts of learning that have been provided to the teachers in their graduation and later professional development, considering that profession development requires a reflection on the teachers´ own learning process.